Effectiveness of the Operational System of Islamic People's Banking in Improving Islamic Financing Performance - Rinda Asytuti; Nindya Mutiara Maharani; Nabilatul Fauziyah; Nayla Mafnuzulfa; Alma Khorina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Sharia Rural Banks (BPRS) are sharia financial institutions that play an important role in supporting community economic development through the distribution of sharia-based financing. In carrying out its function as an intermediary institution, the effectiveness of the operational system is a major factor that determines financing performance. This study was motivated by the low efficiency and effectiveness of operations in most BPRS in Indonesia, which has resulted in limited financing coverage and high levels of non-performing financing (NPF). The purpose of this study is to analyze the effectiveness of the BPRS operational system in improving sharia financing performance, as well as to identify obstacles and strategies for improving operational efficiency in the era of financial digitalization. This study uses a descriptive qualitative method with a library research approach. The data used is secondary, obtained from various relevant national and international journals. The data analysis technique uses content analysis to identify themes and patterns that emerge from previous research results on efficiency, risk management, and operational digitalization of BPRS. The results show that the effectiveness of the BPRS operational system has a significant effect on improving Islamic financing performance. Good operational efficiency can reduce costs, expand financing capacity, and strengthen the institution's profitability. However, there are still several major obstacles, such as limited capital, low quality of human resources, and suboptimal financial literacy among the public. In addition, the high level of non-performing financing remains an obstacle to maintaining the financial stability of BPRS. On the other hand, the digitization of operational systems has been proven to improve efficiency, transparency, and accessibility of services, although it is still constrained by technological limitations and human resource adaptation.